2020
DOI: 10.1038/s41467-020-16046-6
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation-guided optogenetic rescue of parkinsonian symptoms

Abstract: Deep brain stimulation (DBS) of the subthalamic nucleus is a symptomatic treatment of Parkinson's disease but benefits only to a minority of patients due to stringent eligibility criteria. To investigate new targets for less invasive therapies, we aimed at elucidating key mechanisms supporting deep brain stimulation efficiency. Here, using in vivo electrophysiology, optogenetics, behavioral tasks and mathematical modeling, we found that subthalamic stimulation normalizes pathological hyperactivity of motor cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 71 publications
0
54
1
Order By: Relevance
“…Similarly, dyskinetic rats exhibit changes in gene expression 23 and an increased activity in about half of the neurons of the motor cortex 24 . In addition, subthalamic deep brain stimulation, which reduce PD symptoms and thus prevent the need of high L-DOPA dosage producing LID, have been proposed to act via an effect on the motor cortex 25, 26 . Likewise, cerebellar cTBS has been shown to exert a control on motor cortex plasticity 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, dyskinetic rats exhibit changes in gene expression 23 and an increased activity in about half of the neurons of the motor cortex 24 . In addition, subthalamic deep brain stimulation, which reduce PD symptoms and thus prevent the need of high L-DOPA dosage producing LID, have been proposed to act via an effect on the motor cortex 25, 26 . Likewise, cerebellar cTBS has been shown to exert a control on motor cortex plasticity 27 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in an optogenetics application, mice were subjected to 3 ms long optostimulation pulses at 67 Hz frequency (473 nm blue laser diode) to treat Parkinson’s disease. 16 …”
Section: Resultsmentioning
confidence: 99%
“…Elsewhere, a fiber optic sensor was demonstrated for the treatment of Parkinson’s disease in mice. 16 …”
Section: Introductionmentioning
confidence: 99%
“…The increased synchrony observed in the EEG activity can be successfully treated with deep brain stimulation (DBS). Recent models have been proposed to investigate new targets for less invasive therapies by elucidating mechanisms supporting DBS [ 185 , 186 ]. Importantly, with the aim of developing novel DBS methods and optimizing the effects of DBS on patients, computational methods demonstrated that an increase in the DBS stimulation frequency tends to produce action potentials with higher variability and reduces significantly the alpha-beta power in almost all brain nuclei.…”
Section: Modeling Diseasesmentioning
confidence: 99%